Applying narrative medicine to prepare empathetic healthcare providers in undergraduate pharmacy education in Singapore: a mixed methods study - Zhe Han; Keith C. Barton; Li-Ching Ho; Kai Zhen Yap; Doreen Su-Yin Tan; Shuh Shing Lee; Constance Xue Rui Neo; Amanda Han Lin Tan; Brian Ming Yao Boey; Charis Jia Yan Soon; Paul J. Gallagher (BMC Medical Education, 2024)
Abstract Background Narrative medicine demonstrated positive impact on empathy in medicine and nursing students. However, this pedagogical approach had not been evaluated in pharmacy education. This study sought to apply and evaluate the narrative medicine approach in extending empathy in Asian undergraduate pharmacy students. Methods Narrative medicine was applied through workshops which used narratives of people with different experiences and perspectives. First-year undergraduate pharmacy students who volunteered and attended these workshops formed the intervention group (N = 31) and the remaining first-year cohort formed the control group (N = 112). A sequential explanatory mixed methods approach was adopted in which quantitative methods were first used to measure impact on pharmacy students’ empathy using the Jefferson Scale of Empathy– Health Professions Student (JSE-HPS), and qualitative methods (i.e. group interviews) were then used to assess pharmacy students’ emotional responses to narratives, and the perspectives of pharmacy students and faculty of this pedagogical approach. Results There was no difference in JSE-HPS scores between intervention and control groups across baseline (i.e. upon matriculation), pre-intervention, and post-intervention timepoints. Pharmacy students in the intervention group had lower scores in Factor 3 (“Standing in People’s Shoes”) following the intervention. Five themes, guided by internal and external factors in cognition, emerged from the Group Interviews: (1) incongruence between students’ motivation and faculty’s perception, (2) learning context, (3) academic context, (4) cognitive system, and (5) affective system. Themes 1, 4 and 5 referred to internal factors such as students’ motivation, perceived learnings, and feelings. Themes 2 and 3 referred to external factors including workshop materials, activities, content, and facilitation. Conclusion This study is the first to demonstrate that pharmacy students engaged with the narrative medicine approach as narratives elicited emotional responses, exposed them to diverse perspectives, and deepened their appreciation of the importance of empathy and complexities of understanding patients’ perspectives. Scaffolded educational interventions using narratives and real-life patient encounters, alongside longitudinal measurements of empathy, are necessary to bring about meaningful and sustained improvements in empathy.